2018
DOI: 10.3390/nu10030299
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Associations of Maternal Dietary Patterns and Postpartum Mental Health in a Multi-Ethnic Asian Cohort: The Growing up in Singapore towards Healthy Outcomes (GUSTO) Study

Abstract: Diet in the first month postpartum, otherwise known as “the confinement diet” in Asia, has unique characteristics that are influenced by traditions, cultures, and beliefs. We aimed to characterize dietary patterns during confinement period in a multi-ethnic Asian cohort and examined their associations with postpartum depression (PPD) and anxiety (PPA). Dietary intakes of 490 women were ascertained in the first month postpartum using 3-day food diaries and dietary patterns were derived by factor analysis. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 60 publications
(84 reference statements)
0
52
0
Order By: Relevance
“…Six studies examined usual dietary intake during pregnancy [26, 27, 3032, 35]. Two studies [28, 29] evaluated 6 months prior to pregnancy, whereas two other studies evaluated in the postpartum period [33, 34]. The survey methods used included a food frequency questionnaire ( n = 7) [2630, 32, 33], food history questionnaire ( n = 2) [31, 35], and 3-day food record ( n = 1) [34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies examined usual dietary intake during pregnancy [26, 27, 3032, 35]. Two studies [28, 29] evaluated 6 months prior to pregnancy, whereas two other studies evaluated in the postpartum period [33, 34]. The survey methods used included a food frequency questionnaire ( n = 7) [2630, 32, 33], food history questionnaire ( n = 2) [31, 35], and 3-day food record ( n = 1) [34].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [28, 29] evaluated 6 months prior to pregnancy, whereas two other studies evaluated in the postpartum period [33, 34]. The survey methods used included a food frequency questionnaire ( n = 7) [2630, 32, 33], food history questionnaire ( n = 2) [31, 35], and 3-day food record ( n = 1) [34]. For statistical analysis, nine studies used factor analysis [2735] and one used cluster analysis for evaluation of dietary pattern [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity and specificity of EPDS were 65-100% and 49-100%, respectively [ 25 ]. EPDS has been translated and validated for non-English speaking population [ 26 , 27 ] and has used widely in Asian [ 28 , 29 ]. New mothers were also asked to report information about demographics, pregnancy and disease history, interpersonal skill, and characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Yet studies on the relationship between obesity and mental health seem insufficient so far. Among the existing research on this topic, Teo et al [36] investigated the correlation between mental health and food intake during the postpartum period, but the variables were not linked with BMI. Hence, limited evidence from previous studies focusing on mental health effects on postpartum obesity could be found.…”
Section: Previous Studies In Postpartum Obesity Modellingmentioning
confidence: 99%